You need to find t in terms of x and then you should substitute the expression in terms of x for t in equation `y = ln(1 - t)` such that:

`x = t^3 =gt x^(1/3) = (t^3)^(1/3) =gt root(3) x = t`

`y = ln(1 - root(3) x)`

You need to find `(dy)/(dx), ` hence you need to use chain rule such that:

`(dy)/(dx) = ((1 - root(3) x)')/(1 - root(3) x)`

`(dy)/(dx) = -((1/3)*x^(1/3 - 1))/(1 - root(3) x)`

`(dy)/(dx) = -((1/3)*x^(-2/3))/(1 - root(3) x)`

`(dy)/(dx) = -1/(3*x^(2/3)*(1 - root(3) x))`

`(dy)/(dx) = -1/(3*root(3)(x^2)*(1 - root(3) x))`

**Hence, evaluating `(dy)/(dx)` under given conditions yields `(dy)/(dx) = -1/(3*root(3)(x^2)*(1 - root(3) x)).` **